KARAKTERISASI SCOBY (SYMBIOTIC CULTURE OF BACTERIA AND YEAST) DAN DAYA TERIMA KEFIR AIR KELAPA NANAS - Novianty Novianty (IKesT Muhammadiyah Palembang, 2024)
Introduction: Scoby (Symbiotic culture of bacteria and yeast) are a group of microorganisms found in probiotic drinks. The presence of these microorganisms in drinks adds nutritional value which is beneficial for the human body. Scoby is found in kefir-type probiotic drinks. Kefir in circulation only contains milk and has not been fortified with fruit juice, even though the addition of fruit juice can increase the nutrients, aroma, taste and texture. Coconut and pineapple water could be used as additional ingredients in making kefir. Not many studies have reported on coconut and pineapple water kefir. Objective: to get the right formulation, find out the characteristics of the scoby, and the acceptability of pineapple coconut water kefir. Method: This research is experimental research. with 3 treatments with 10 repetitions. The data obtained included the characteristics of scoby kefir, the number of LAB, and the acceptability of pineapple coconut water kefir based on organoleptic tests. Results: The results show that the characteristics of the pineapple coconut water kefir scoby are lactic acid bacteria (LAB) and yeast. The best total amount of BAL was in P3 with a total of 281 CFU/mL, and organoleptic tests based on aroma, texture, color parameters were found in P2 and taste in P3. Conclusions: The best formulation of pineapple coconut water kefir is P2, pineapple coconut water kefir consists of BAL and scoby. The panelists' acceptance based on color is in P2 and taste is in P3